DIVERSITY OF ECONOMICALLY VALUABLE FISH TYPES IN THE LUBUK LARANGAN AREA, THE BATANG BUNGO RIVER, BUNGO REGENCY, JAMBI - Rini Hertati; Safitriani Safitriani (Asian Journal of Aquatic Sciences, 2025)
The diversity of economically valuable fish species in the Batang Bungo River is crucial for assessing the condition and population, which is the foundation for sustainable capture fisheries in the future. The research aims to identify the economic value of the Batang Bungo River and the diversity, dominance, and relative abundance of economically valuable fish. The research method involved a survey, and data were collected using a purposive sampling technique based on various environmental characteristics and fishing areas commonly used by local fishermen. These fishermen caught 15 people per station. Eight species of economically valuable fish were found in the Batang Bungo River. The diversity values ​​in the upstream (2,049) and downstream (1,933) sections were categorized as moderate. Dominance Index of upstream (0.13: downstream section: 0.15) (medium). The highest relative abundance was found in seluang (Rasbora argyrotaenia) (relative value: 15,95%) and baung (Mystus nemurus) (relative value: 15,65%).